2009
DOI: 10.1111/j.1365-2559.2009.03398.x
|View full text |Cite
|
Sign up to set email alerts
|

CD10+ fibroblasts are more involved in the progression of hilar/extrahepatic cholangiocarcinoma than of peripheral intrahepatic cholangiocarcinoma

Abstract: We suggest that CD10+ fibroblasts are more involved in the progression of hilar and extrahepatic CC than of peripheral intrahepatic CC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…In another study that examined biliary dysplasia and cholangiocarcinomas of both intrahepatic and extrahepatic locations, CD10 expression was limited to stromal fibroblasts in 27.5% of cases, but dysplastic/neoplastic epithelium was uniformly negative. 25 It is interesting to note that stromal expression of CD10 is associated with biological aggressiveness of various tumors, including pancreatobiliary carcinomas, by enhancing tumor progression. 16 In our study, CD10 expression was not commonly observed in stromal fibroblasts, presumably because of the superficial nature of the biopsy specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study that examined biliary dysplasia and cholangiocarcinomas of both intrahepatic and extrahepatic locations, CD10 expression was limited to stromal fibroblasts in 27.5% of cases, but dysplastic/neoplastic epithelium was uniformly negative. 25 It is interesting to note that stromal expression of CD10 is associated with biological aggressiveness of various tumors, including pancreatobiliary carcinomas, by enhancing tumor progression. 16 In our study, CD10 expression was not commonly observed in stromal fibroblasts, presumably because of the superficial nature of the biopsy specimens.…”
Section: Discussionmentioning
confidence: 99%
“…4,32 In contrast, intrahepatic cholangiocarcinomas were negative to CD10. 18,19,23,25,36 However, the expression profile of CD10 in benign and malignant epithelial lesions of the extrahepatic biliary tree has not been studied. Therefore, we aimed to investigate CD10 expression on reactive atypia (RA) and low-grade dysplasia (LGD) and high-grade dysplasia (HGD), in comparison with adenocarcinoma, and evaluate its potential diagnostic utility.…”
mentioning
confidence: 99%
“…Besides hemato‐lymphoid organs, CD10 is widely distributed in epithelial cells and stromal cells of human tissues, including in the brain, lung, kidney, intestine and male genital tract . Concordantly, CD10 is expressed in a variety of epithelial cancers including carcinoma of the prostate, kidney, breast, lung, stomach, liver, thyroid and skin . Furthermore, high expression of CD10 has been demonstrated to be associated with aggressive behavior of several types of cancer, especially in malignant melanoma and prostate cancer .…”
mentioning
confidence: 99%
“…CD10 is expressed on some normal and neoplastic haemopoietic, lymphoid and epithelial cells (13). CD10 expression has also been detected in tumor associated stromal cells indicating its vital role in tumor-stromal interactions (14).…”
Section: Discussionmentioning
confidence: 99%